Clinical validity of repeated circulating tumor cell enumeration as an early treatment monitoring tool for metastatic breast cancer in the PREDICT global pooled analysis - Janni, Wolfgang; Friedl, Thomas W.P.; Yab, Tracy C.; Bidard, Francois-Clément; Cristofanilli, Massimo; Hayes, Daniel F.; Ignatiadis, Michail; Regan, Meredith M.; Alix-Panabieres, Catherine; Barlow, William E.; Caldas, Carlos; Carey, Lisa A.; et al. (Clinical cancer research, 2025)
The aim of PREDICT was to confirm clinical validity and the potential for clinical utility of serial circulating tumor cell (CTC) enumeration in patients with metastatic breast cancer, focusing on its prognostic value in different breast cancer subtypes and clinical settings.In total, 4,436 individual patient-level data with CTC results from both baseline and one follow-up (CellSearch; Menarini Silicon Biosystems) were analyzed to evaluate the association between CTC detection and overall survival (OS) in the full patient cohort and separately for tumor and treatment types.Using the cutoff ≥1 CTC for CTC positivity, 913 (20.6%) patients had 0 CTCs at both time points (neg/neg) and 325 (7.3%) and 1,189 (26.8%) patients converted from CTC negative to CTC positive (neg/pos) or vice versa (pos/neg), whereas 2,009 (45.3%) patients had at least one CTC at both time points (pos/pos). The median OS for the neg/neg, neg/pos, pos/neg, and pos/pos group was 45.6, 26.1, 32.3, and 17.3 months, respectively (P < 0.0001, global log-rank test). CTC responders (pos/neg) showed a lower risk of death compared with CTC nonresponders (pos/pos; HR, 0.48; 95% confidence interval, 0.44-0.53). Similar results were obtained in subgroup analyses according to hormone receptor and HER2 subtype, treatment type, and with a ≥5 CTC cutoff for CTC positivity.Follow-up CTC assessments strongly predict OS independently from tumor subtype and treatment. New randomized trials to define the clinical utility of CTC monitoring for risk stratification and as an early response marker in metastatic breast cancer are urgently needed.
Veröffentlicht: 3. Juni 2025
Gesehen am 25.09.2025